Drep-2 is a novel synaptic protein important for learning and memory - Till F M Andlauer; Sabrina Scholz-Kornehl; Rui Tian; Marieluise Kirchner; Husam A Babikir; Harald Depner; Bernhard Loll; Christine Quentin; Varun K Gupta; Matthew G Holt; Shubham Dipt; Michael Cressy; et al. (eLife, 2014)
CIDE-N domains mediate interactions between the DNase Dff40/CAD and its inhibitor Dff45/ICAD. In this study, we report that the CIDE-N protein Drep-2 is a novel synaptic protein important for learning and behavioral adaptation. Drep-2 was found at synapses throughout the Drosophila brain and was strongly enriched at mushroom body input synapses. It was required within Kenyon cells for normal olfactory short- and intermediate-term memory. Drep-2 colocalized with metabotropic glutamate receptors (mGluRs). Chronic pharmacological stimulation of mGluRs compensated for drep-2 learning deficits, and drep-2 and mGluR learning phenotypes behaved non-additively, suggesting that Drep 2 might be involved in effective mGluR signaling. In fact, Drosophila fragile X protein mutants, shown to benefit from attenuation of mGluR signaling, profited from the elimination of drep-2. Thus, Drep-2 is a novel regulatory synaptic factor, probably intersecting with metabotropic signaling and translational regulation.